Pengaruh Media Pembelajaran Digital Untuk Meningkatkan Keterampilan Dasar Sepak Bola Siswa Sekolah Dasar - Frananta Edisyah Putra Sembiring; Muchamad Arif Al Ardha; Mochamad Ridwan (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2026)
This study aims to analyze the effect of digital learning media on improving elementary school students' basic soccer skills. This study used an experiment with a pretest-posttest control group design. This study was conducted at an elementary school in Halmahera Regency. The sample used in this study was class V-a, consisting of 40 students. Data analysis in this study will be conducted by describing the data, testing the prerequisites for analysis, and testing the hypothesis with a t-test. The research instrument is a rubric for assessing students' dribbling skills. The results of the t-test show that all Fh values ​​> Ft (1.68), so Ho is rejected and there is a significant difference. The results show that both image-based learning media and digital learning media contribute to improving the basic soccer skills of elementary school students. To improve the basic soccer skills of elementary school students, digital learning media is more effective than image-based media.